Inflation in Britain: A Monetarist Perspective: Comment - Fane, George (American Economic Review, 1978)
David Laidler recently presented a perspective on British inflation in this Review. His analysis incorporated two distinctively monetarist propositions: first, the adaptive expectations version of the natural rate hypothesis (NRH), according to which there is no permanent tradeoff between inflation and unemployment, since events which cause unemployment to fall below the natural rate of unemployment (NRU) also cause the actual inflation rate to exceed the expected inflation rate, and vice versa; and second, the claim (p. 487) that, at least since 1968, variations in the rate of monetary growth have caused short-run variations in real activity and unemployment. Combining these propositions Laidler argued that variations in the rate of monetary growth determine variations in the rate of inflation. His article attempted to use this model to explain the variations in inflation and unemployment in Britain since 1953, and in particular to diagnose the causes of the failure of Keynesian policies after 1967 despite their apparent earlier success. In explaining Britain's recent experience of high inflation and historically high unemployment Laidler did not attribute any role to cost-push forces associated with union militancy or with rises in import prices. This note criticizes Laidler's analysis on four grounds: 1) he underestimates the difficulties of reconciling NRH with the facts; 2) contrary to the second of the two distinctively propositions listed above, variations in the rate of growth of the money supply have not been closely correlated with changes in real activity; 3) his explanation for the failure of Keynesian fiscal policies after 1967, despite their apparent success before 1967, is wrong; and 4) Laidler is wrong to minimize or deny the contribution to Britain's depressing record of high inflation and high unemployment in the 1970's, of increases in union power and militancy and of increased world prices of imported raw materials. These points are dealt with in the next four sections. The conclusions are given in the last section.